The effect of Vitamin D treatment on thyroid function and the levels of thyroid autoantibodies, TNF-?, IL-6, IL-1? in patients with autoimmune thyroiditis - Acıbucu, Fettah; Dökmetaş, Hatice Sebile; Kılıçlı, Fatih; Çelik, Cem; Aydemir, Mustafa (Sivas Cumhuriyet University, 2016)
Objective: To investigate the relationship between autoimmune thyroid disease and vitamin D treatment. Method: Fifty four (54) patients with both vitamin D deficiency and newly diagnosed euthyroid Hashimoto's thyroiditis (HT) were recruited for this study. The patients were given intramuscular administration of cholecalciferol at a dose of 300,000 IU/month for 3 months. At the time of diagnoses and after the treatment of vitamin D, free T3 (FT3), free T4 (FT4), thyroid stimulating hormone (TSH), antithyroid peroxidase (anti-TPO), antithyroglobulin (anti-TG), 25 (OH) D3, parathormone (PTH), calcium (Ca), phosphorus (P) and alkaline phosphatase (ALP) levels were measured in all patients; TNF-a, IL-6 and IL-1ß levels were measured in only 43 patients. Results: A statistically significant difference (p?0.05) was observed between the pre and post treatment FT4, TSH, antiTPO, antiTG, PTH and ALP levels. After the treatment of vitamin D, a statistically significant increase was found in 25 (OH) D3 and FT4 levels, and a significant decrease was found in TSH, antiTPO, antiTG, PTH and ALP levels, whereas no significant difference was noted in FT3, Ca, P, TNF- a, IL-6 and IL-1ß levels. Further, levels of vitamin D were not correlated with FT3, FT4, TSH, antiTPO, antiTG, TNF-a, IL-6 and IL-1ß levels (p?0.05). Conclusions: For patients with both vitamin D deficiency and newly diagnosed HT, treatment of vitamin D had a positive effect on the thyroid antigenicity and thyroid function.

Amaç: D vitamini tedavisinin otoimmun tiroid hastalığı ile ilişkisini araştırdık. Yöntem: Çalışmaya D vitamini yetersizliği ve beraberinde yeni tanı alan Hashimoto tiroiditi olan (HT) 54 hasta alındı. Hastalara 3 ay süreyle ayda bir 300.000 IU kolekalsiferol intramuskuler olarak verildi. Tanı esnasında ve D vitamini tedavisi sonrasında serbest T3(FT3), serbest T4 (FT4), tiroid stimulan hormon (TSH), anti tiroid peroksidaz (TPO) ve anti tiroglobulin (TG), 25(OH)D3, parathormon (PTH), kalsiyum (Ca), fosfor (P) ve alkalen fosfataz (ALP) seviyeleri ve yalnız 43 hastada TNF- ?, IL-6, IL-1b seviyeleri ölçüldü. Bulgular: Tedavi öncesi ve sonrası FT4, TSH, antiTPO, antiTG, PTH ve ALP seviyeleri açısından arada istatistiksel olarak anlamlı fark vardı (p<0.05). D vitamini tedavi sonrasında 25 (OH) D3 ve FT4 seviyelerinde istatiksel olarak önemli bir artış olurken TSH, antiTPO, antiTG, PTH ve ALP seviyelerinde ise önemli bir düşüş gözlendi. FT3, Ca, P, TNF- ?, IL-6 ve IL-1b açısından önemli bir fark yoktu. D vitamini seviyesi ile FT3, FT4, TSH, antiTPO, antiTG, TNF- ?, IL-6 ve IL-1b arasında bir korelasyon yoktu. Sonuç: D vitamini eksikliği ve yeni tanı HT'i olan hastalarda D vitamini tedavisinin tiroid antijenitesi ve tiroid fonksiyonu üzerine olumlu yönde etkisi vardır.
Otoimmun tiroiditi bulunan hastalarda D vitamini tedavisinin tiroid fonksiyonları ve tiroid otoantikorları, TNF-?, IL-6, IL-1? düzeyleri üzerine etkisi
Keywords: Autoimmune Thyroid Disease; Hashimoto's Thyroiditis; Vitamin D Deficiency; Otoimmun Tiroid Hastalığı; Hashimoto Tiroiditi; D Vitamini Yetersizliği